Assessing Monthly Progress towards Annual Fiscal Revenue Targets - Kanda, Daniel (Washington, D.C. : International Monetary Fund, 2002)
A simple statistical methodology is developed to help evaluate monthly progress toward an annual fiscal revenue target, and the applicability of the methodology to both developing and industrial countries is demonstrated using data for Sri Lanka and the United States.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet